Den Norske Sydpol-ekspedisjonen 1990-91 (Polarboken, 1992)
Keywords: Antarktis; ekspedisjoner

Executive summary: November 1992 (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; litteratur; politikk

ATS decision-making and change: the role of domestic politics in Australia - Davis, Bruce W; Herr, Richard A (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; politikk

The climate of Halley, Antarctica - Hanssen-Bauer, Inger; DNMI (Det norske meteorologiske institutt, 1992)
Keywords: Antarktis; klima; meteorologi

Antarctica and non-state actors: the question of legitimacy - Herr, Richard A; Davis, Bruce W (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; politikk

Into the heart of the Antarctic - Imbert, Bertrand C (North Pole, South Pole : journeys to the ends of the earth, 1992)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

The role of domestic politics in making United States Antarctic policy - Joyner, Christopher C (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; politikk

Activities within the Aurora Programme field season 1991/92 - Kristensen, Monica (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Antarktis; ekspedisjoner; glasiologi; meteorologi

Negotiating the mineral regime in the Antarctic: a review - Mørkved, Berit (International Challenges, 1992)
Keywords: Antarktis; jus; mineraler; politikk

Bunnvannsstrømmer på kontinentalskråningen i Weddellhavet - Nordlund, Nina (Universitetet i Bergen, 1992)
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; havstrømmer; oseanografi

En modell for sirkulasjonen under isshelfene i Weddelhavet og Rosshavet - Nøst, Ole Anders (O. A. Nøst, 1992)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Gigantisk isfjell i Sør-Atlanteren - Orheim, Olav (Polarboken, 1992)
Keywords: Sørishavet; glasiologi; isfjell

The protection of the Antarctic environment - Orrego Vicuña, Francisco (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; miljøvern

Studies through Jutulgryta, Fimbulisen in the 1991/92 season - Østerhus, Svein; Orheim, Olav (Filchner-Ronne Ice Shelf Programme. Report, 1992)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; oseanografi

Pertusaria signyae (Lichenes), a new species from the Antarctic - Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A saxicolous Pertusaria species is described as new to science: P. signyae Ovst. from South Orkney Islands. It has an isidiate thallus, subglobose fertile verrucae with poriform apothecia, and contains 2'-0-methylperlatolic acid.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

Contributions to the Caloplaca flora of the western Antarctic region - Søchting, Ulrik; Øvstedal, Dag Olav (Nordic Journal of Botany, 1992)
Fourteen species of the lichen genus Caloplaca are recorded from the western Antarctic region and described morphologically and anatomically, viz.: C. ammiospila, C. approximata, C. athallina, C. cirrochrooides, C. citrina, C. isidioclada, C. lucens, C. millegrana, C. regalis, C. sublobulata, C. tenuis, C. aff. anchon-phoeniceon. Type specimens of critical species have been studied. A key is provided to the species. Caloplaca ammiospila and C. approximata are reported as new to the Antarctic region.
Keywords: Antarktis; botanikk; lav; planter

Bouvetøya: et norsk naturreservat - Sømme, Lauritz (Fauna, 1992)
Keywords: Bouvetøya; fauna; forvaltning; natur

Domestic politics and non-state actors in the Antarctic Treaty System: towards a framework - Stokke, Olav Schram (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; jus; politikk

Protecting the frozen south - Stokke, Olav Schram (Green globe yearbook, 1992)
Keywords: Antarktis; jus; miljøvern; politikk

Eine neue Gyalecta-Art aus der Antarctis: G. pezizoides sp. n. (lichensierte Fungi, Gyalectaceae) - Vezda, A.; Øvstedal, Dag Olav; Smith, Ronald I Lewis (Nova Hedwigia, 1992)
A new species of the genus Gyalecta, G. pezizoides sp. n. (lichenized Fungi, Gyalectaceae), is described and illustrated. This new species is taxonomically near to the holarctic Gyalecta peziza (Mont.) Anzi.
Keywords: Antarktis; botanikk; lav; planter

Antarctic tourism: a challenge to the legitimacy of the Antarctic Treaty System? - Vidas, Davor (Fridtjof Nansens institutt, 1992)
Keywords: Antarktis; turisme